Design and construct discrete compound parabolic concentrator integrated collector storage solar water heater (CPC ICSSWH) - Khong, Dewitt (2018)
Solar energy is clean, free and sustainable compared to fossil fuels. One of the typical utilization of solar energy is solar water heating system where it is a welldeveloped application for water heating. There are numerous types of solar water heater (SWH) systems existed in the market to suit customers’ various demands. For instance, flat plate collector SWH, evacuated tube collector SWH, parabolic trough collector SWH and integrated collector storage SWH. This study presents a discrete compound parabolic concentrator integrated collector storage solar water heater (CPC ICSSWH) that is easy to be fabricated and it is a passive system in which active pump and sun tracking is not required. The discrete compound parabolic concentrator (CPC) was constructed by several rectangular facet mirrors and a wide acceptance angle of 56° was used so that sun tracking can be eliminated, thus making it very suitable for domestic purposes. Ray tracing simulation, system performance analysis and the cost analysis of the discrete CPC ICSSWH were carried out and presented in details. The discrete CPC ICSSWH can achieve a theoretical maximum system efficiency of 63.39% and has attained highest water temperature of 70.6°C with total payback period of 6.25 years.